Building organisational resilience for the construction industry: New Zealand practitioners' perspective. Issue 1 (13th February 2017) - Sapeciay, Zulkfli; Wilkinson, Suzanne; Costello, Seosamh B.
Abstract : Purpose: This paper aims to explore New Zealand construction practitioners' approaches to organisational resilience practice in built environment discipline, based on survey and interview results. The objective was to explore the resilience practice within the construction sector with the intention of developing a resilient assessment tool specifically for construction organisations. Design/methodology/approach: A literature review was conducted to gather information on assessment tools for measuring organisational resilience, their characteristics and indicators. Subsequently, a set of questions was formulated to collate opinions from construction practitioners in New Zealand, using a questionnaire survey and semi-structured interviews. Findings: This paper concludes by showing that the construction industry lacks resilience practice, especially from an organisational perspective. The findings suggest that the industry would benefit from a resilience assessment tool to help improve resilience. The adoption of such a tool could potentially enhance organisational capacity to recover quickly from crises and disasters. Practical implications: Improving the resilience of construction organisations to natural disasters not only minimises the negative consequences to their organisations post-disaster and enhances their organisational performance during business as usual but also helps to improve community resilience. Originality/value: Improving the resilience of construction organisations also helps to improve community resilience and overall post-disaster recovery. However, at present, little research has been conducted on how construction organisations deal with the risk of natural disasters.